Mast cell heterogeneity and anti-inflammatory annexin A1 expression in leprosy skin lesions - Costa, Mauricio B.; Mimura, Kallyne K. O. [UNESP]; Freitas, Aline A.; Hungria, Emerith M.; Sousa, Ana Lucia O. M.; Oliani, Sonia M. [UNESP]; Stefani, Mariane M. A. (Elsevier B.V., 2018)
Mast cells (MCs) have important immunoregulatory roles in skin inflammation. Annexin A1 (ANXA1) is an endogenous anti-inflammatory protein that can be expressed by mast cells, neutrophils, eosinophils, monocytes, epithelial and T cells. This study investigated MCs heterogeneity and ANXA1 expression in human dermatoses with special emphasis in leprosy. Sixty one skin biopsies from 2 groups were investigated: 40 newly diagnosed untreated leprosy patients (18 reaction-free, 11 type 1 reaction/T1R, 11 type 2 reaction/T2R); 21 patients with other dermatoses. Tryptase/try + and chymase/chy + phenotypic markers and toluidine blue stained intact/degranulated MC counts/mm(2) were evaluated. Try(+)/chy(+) MCs and ANXA1 were identified by streptavidin-biotin-peroxidase immunostaining and density was reported. In leprosy, degranulated MCs outnumbered intact ones regardless of the leprosy form (from tuberculoid/TT to lepromatous/LL), leprosy reactions (reactional/reaction-free) and type of reaction (T1R/T2R). Compared to other dermatoses, leprosy skin lesions showed lower numbers of degranulated and intact MCs. Try(+) MCs outnumbered chy(+) in leprosy lesions (reaction-free/reactional, particularly in T2R), but not in other dermatoses. Compared to other dermatoses, ANXA1 expression, which is also expressed in mast cells, was higher in the epidermis of leprosy skin lesions, independently of reactional episode. In leprosy, higher MC degranulation and differential expression of try(+)/chy(+) subsets independent of leprosy type and reaction suggest that the Mycobacterium leprae infection itself dictates the inflammatory MCs activation in skin lesions. Higher expression of ANXA1 in leprosy suggests its potential anti-inflammatory role to maintain homeostasis preventing tissue and nerve damage.
Keywords: Mast cell; Annexin A1; Tryptase; Chymase; Leprosy; Skin diseases